Coronoid nanographene C216 as hydrogen purification membrane: A density functional theory study. (August 2018) - Liu, Yi; Liu, Wei; Hou, Jian; Dai, Yafei; Yang, Jinlong
Abstract: The first coronoid nanographene C216 molecule, which is an extended polycyclic aromatic hydrocarbon containing a defined cavity, was studied throughly as a hydrogen purifier using the density functional theory and molecular dynamics simulations. It is demonstrated that C216 is an effective ultimate membrane for hydrogen purification with a moderate penetrating energy barrier of about 0.615 eV. Furthermore, C216 is superior to the porous graphene, polyphenylene, and other traditional membranes since the selectivity of H2 to O2, N2, NO, H2 O, CO and CO2 on C216 surface is higher than other membranes. Meanwhile, the recent successful synthesis of nanographene C216 in the laboratory provides the possibility of the industrial applications. Graphical abstract: Image